Diagnosis of Cardiovascular Renal Axis Disorder Subtype Hin Non-azotemic dogs - Ghag, Rupalee S.; Unny N., Madhavan; Pillai, Usha N.; S., Ajithkumar; K. D., John Martin; M., Shynu. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Two types of cardiac disorders, viz Dilated cardiomyopathy (DCM) and acquired valvular disease, were diagnosed in dogs. Thirty non azotemic dogs with clinical signs suggestive of cardiovascular dysfunction formed part of this study. Standard treatment regimens as required were administered during the study. Serum inosine, urine specific gravity, and microalbumin were the renal biomarkers evaluated to diagnose these dogs’ cardiovascular renal axis disorder subtype H (CvRDH). A decline in serum inosine values on day 45 as compared to day 0 was suggestive of reduced renal functional status. Lowered urine-specific gravity in these non-azotemic dogs indicated renal dysfunction. Urine microalbumin values documented were consistent with microalbuminuria,which proved to be a reliable biomarker of glomerular damage and developing nephropathy. The renal biomarkers aided in the diagnosis of CvRDH in these dogs.